EU copyright law : a commentary - Stamatoudi, Irini A.; Torremans, Paul, 1965- (Elgar commentaries, 2021)
This significantly revised and updated second edition addresses the rapid development of EU copyright law in relation to the advancement of new technologies, the need for a borderless digital market and the considerable number of EU legal instruments enacted as a result. Taking a comparative approach, the Commentary provides comprehensive coverage and in-depth commentary on each of the EU legal instruments and policies, both from an EU and an international perspective. Alongside full legislative analysis and article-by-article commentary, the Commentary illustrates the underlying basic principles of free movement and non-discrimination and provides insights into the influence of copyright on other areas of EU policy, including telecoms and bilateral trade agreements.